Computer Intensive Methods for Testing Hypotheses / An Introduction - Noreen Eric W (John Wiley And Sons, Inc, 1989)
Preface, Introduction, Approximate Randomization Tests, Monte Carlo Sampling, Bootstrap Resampling, Conclusion, Appendices, BASIC Programs, FORTRAN Programs, PASCAL Program, Probability Tables, References, Index.